2022
DOI: 10.1177/24730114221101617
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Nonunion and Infection Following Ankle Arthrodesis Using a Large Claims Database: Who Has Elevated Risk?

Abstract: Background: Complications such as nonunion and infection following ankle arthrodesis can lead to increased patient morbidity and financial burden from repeat operations. Improved knowledge of risk factors can improve patient selection and inform post–ankle arthrodesis surveillance protocols. Methods: This is a large retrospective, database study with structured query of a national insurance claims database (PearlDiver Technologies) for patients treated with ankle arthrodesis from 2015 to 2019 as identified by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Analysis of a large administrative claims database of 2463 patients identified that nonunion occurred in 14% of patients following ankle arthrodesis, and the odds of nonunion were higher among patients with a smoking record compared to patients without (18.0% vs 12.8%). 38 A recent systematic review and meta-analysis of ankle arthrodesis studies has also identified smoking (OR 2.89, 95% CI 1.23-6.76) as a factor associated with nonunion. 30 In our study, other patient variables such as concomitant steroid use and history of inflammatory arthropathy had relatively high impact on the OR in the univariate analysis without a significant P value.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Analysis of a large administrative claims database of 2463 patients identified that nonunion occurred in 14% of patients following ankle arthrodesis, and the odds of nonunion were higher among patients with a smoking record compared to patients without (18.0% vs 12.8%). 38 A recent systematic review and meta-analysis of ankle arthrodesis studies has also identified smoking (OR 2.89, 95% CI 1.23-6.76) as a factor associated with nonunion. 30 In our study, other patient variables such as concomitant steroid use and history of inflammatory arthropathy had relatively high impact on the OR in the univariate analysis without a significant P value.…”
Section: Discussionmentioning
confidence: 99%
“…The only study to identify obesity as a risk factor for nonunion was the analysis of a large administrative claims database mentioned above that identified that odds of nonunion were higher in obese patients compared with nonobese patients (17.1% vs 9.5%). 38 One case series of open ankle fusions found nonunion was associated with varus ankle alignment. 5 Two further case series of AAA found no difference in union rates associated with preoperative varus/valgus ankle deformity of >15 degrees.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11,[32][33][34] It is also likely that some of the factors identified, particularly comorbidities, are general operative risk factors which may similarly influence the outcome of alternative operative treatments such as ankle arthrodesis. [35][36][37] Therefore, rather than using individual identified factors as contraindications, clinicians should incorporate a holistic assessment of patient risk factors, evaluating the presence and number of these to aid in both clinical decision-making and informing patient expectations. Future research should continue to aid this process, ensuring that adequate statistical techniques are used to control for confounding factors when attempting to identify independent risk factors for poorer outcome.…”
Section: Discussionmentioning
confidence: 99%